Achieving Sustainable Development Goals in Nigeria's power sector: assessment of transition pathways. (8th August 2020) - Yetano Roche, María; Verolme, Hans; Agbaegbu, Chibuikem; Binnington, Taylor; Fischedick, Manfred; Oladipo, Emmanuel Olukayode
ABSTRACT: Nigeria is Africa's largest economy and home to approximately 10% of the un-electrified population of Sub-Saharan Africa. In 2017, 77 million Nigerians or 40% of the population had no access to affordable, reliable and sustainable electricity. In practice, diesel- and petrol-fuelled back-up generators supply the vast majority of electricity in the country. In Nigeria's nationally-determined contribution (NDC) under the Paris Agreement, over 60% of the greenhouse gas emissions (GHG) reductions are foreseen in the power sector. The goal of this study is to identify and critically examine the pathways available to Nigeria to meet its 2030 electricity access, renewables and decarbonization goals in the power sector. Using published data and stakeholder interviews, we build three potential scenarios for electrification and growth in demand, generation and transmission capacity. The demand assumptions incorporate existing knowledge on pathways for electrification via grid extension, mini-grids and solar home systems (SHS). The supply assumptions are built upon an evaluation of the investment pipeline for generation and transmission capacity, and possible scale-up rates up to 2030. The results reveal that, in the most ambitious Green Transition scenario, Nigeria meets its electricity access goals, whereby those connected to the grid achieve a Tier 3 level of access, and those served by sustainable off-grid solutions (mini-grids and SHS) achieve Tier 2. Decarbonization pledges would be surpassed in all three scenarios but renewable energy goals would only be partly met. Fossil fuel-based back-up generation continues to play a substantial role in all scenarios. The implications and critical uncertainties of these findings are extensively discussed. Key policy insights The 2030 electricity mix for Nigeria varies across the scenarios presented, with the most ambitious scenario achieving electricity access goals and partly meeting renewable energy goals. All three scenarios surpass the decarbonization targets of Nigeria's NDC for the power sector. The transformation of the power sector relies on a wide range of financial, policy and enabling environment-related conditions taking place in the near-term, some of which are in turn strongly influenced by larger political economy realities. Fossil fuel-based back-up generation plays a substantial role in all scenarios. Data availability for this technology remains a significant source of uncertainty. GRAPHICAL ABSTRACT: UF0001